PENGARUH LAJU ALIRAN UDARA TERHADAP KINERJA SISTEM REFRIGERASI PADA TATA UDARA SENTRAL - M. Nuriyadi (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2016)
The work of refrigeration system incentral air conditioning should be set to the cooling load to obtain the peak performance of the system with efficient energy consumption. One factor that affect to the the cooling load is the conditioned air flow rate suppliedin the system.The experiment is conducted by varying air flow rate (with 4 variations which is 1,152; 1,184; 1,216 and 1,280 m3/s respectively), to aim the optimum performance of the refrigeration system in the air conditioning system (central AHU) to consumption efficient levelof power. The results is that the refrigeration system performance is not much influenced by variations ofair flow rate,where the highest coefficient of performance (COP) of the refrigeration system (5.69) was obtained by air flow rate (debit) of 1,184 m3/s, about 4% of the COP on the largest debit. The highest compression ratio (3.5) was obtained at lowest air flow rate (1.152 m3/s), and the lowest average of power consumption is obtained at the lowest air flow rate 1.152 m3/s, 9% lower than power consumption at thegreatest air flow.While the performance of the HVAC system is affected by variations in air flow rate, where is the greatest cooling capacity (62.364 kW) and the highest EER (3.99) was obtained at the highest flow rate of 1.280 m3/s. Keywords: air flow rate, performance, central air conditioning.